Gender Disparities in Science Labor Supply: Evidence from Sub-Saharan Africa - Guindo, Tidiane; Elpisa, Mike Juni; Bachtiar, Nasri (International Journal of Economics (IJEC), 2025)
This study investigates gender disparities in science-related labor supply preferences in Sub-Saharan Africa (SSA) using ordered logistic regression on data from Wave 7 of the World Values Survey (2017–2022) across Ethiopia, Kenya, Nigeria, and Zimbabwe. Analyzing seven attitudinal indicators toward science and technology, the findings reveal no evidence that women hold less favorable views than men; in some cases, women exhibit stronger pro-science attitudes. Key factors such as religiosity and education significantly influence science preferences, with higher education correlating positively and religiosity negatively, particularly in science-religion conflicts. The results suggest that structural barriers—not intrinsic gender differences in preferences—likely drive women's underrepresentation in STEM fields. Policy interventions should focus on dismantling institutional and socio-cultural constraints to enhance gender equity in SSA's science workforce.